A Study to Investigate the Impact of Spiritual Leadership on Inclusion Practices: An Empirical Evidence through Mediated Mediation Approach - Waqas Khaliq Bhatti (Journal of Peace, Development and Communication, 2023)
Spiritual leadership plays a vital role in reaping positive benefits of diversity through creating healthier work places. Spiritual leadership style is for a diversified workplaces is gaining much attention in management sciences research owing to its unique way of improving workplace spirituality and employees’ performance. This research provides evidence of the key role of spirituality (i.e., spirituality leadership, workplace spirituality) plays in inclusion practices and climate for inclusion. The objective is to determine whether and to what extent Spiritual leadership is appropriate in the MNC’s context operating in Pakistan. The sample size of the study consisted of multinational companies operating in selected cities of Pakistan. There are almost 380 multinational companies are operating in Islamabad and Rawalpindi. The unit of analysis of this study consisted of managerial level employees of multinational organization operating in Pakistan. This research used a probability-based, simple random selection strategy to choose 380 participants for questionnaire completion. Results of the study revealed that Spiritual leadership has significant positive relationship with inclusion practices, whereas workplace spirituality has significant positive mediation role among them. Moreover, Spiritual leadership has significant positive relationship with climate for inclusion, however, mediation role of inclusion practices among these have not been validated.